2014
DOI: 10.1002/hon.2173
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and high‐dose daunorubicin and idarubicin in acute myeloid leukaemia remission induction treatment: a mixed treatment comparison meta‐analysis of 7258 patients

Abstract: Previous meta-analyses suggested that acute myeloid leukaemia induction regimens containing idarubicin (IDA) or high-dose daunorubicin (HDD) induce higher rates of complete remission (CR) than conventional-dose daunorubicin (CDD), with a possible benefit in overall survival. However, robust comparisons between these regimens are still lacking. We conducted a mixed treatment comparison meta-analysis regarding these three regimens. Mixed treatment comparison is a statistical method of data summarization that agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Metaanalyses of alternative anthracyclines did not suggest that there was a major difference between these agents. 12, 13 Several trials have tested cytosine arabinoside dose modification, again without convincing evidence of benefit. [14][15][16] Our previous trial in younger patients (Medical Research Council [MRC] AML15) demonstrated that the fludarabine/cytosine arabinoside/granulocyte colony-stimulating factor and idarubicin (FLAG-Ida) regimen can deliver a higher number of remissions with the first course and also reduce the risk of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Metaanalyses of alternative anthracyclines did not suggest that there was a major difference between these agents. 12, 13 Several trials have tested cytosine arabinoside dose modification, again without convincing evidence of benefit. [14][15][16] Our previous trial in younger patients (Medical Research Council [MRC] AML15) demonstrated that the fludarabine/cytosine arabinoside/granulocyte colony-stimulating factor and idarubicin (FLAG-Ida) regimen can deliver a higher number of remissions with the first course and also reduce the risk of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, daunorubicin is considered equivalent to idarubicin if the relative dose ratio (daunorubicin/idarubicin) is ≥5. 6 , 7 We found in this study that the most prescribed anthracycline was daunorubicin (60 mg/m 2 ), that is according to current practices.…”
Section: Discussionmentioning
confidence: 66%
“…Other than the former relevant metaanalysis regarding the evaluation of routine treatments, we are the first to conduct an overall comparison among new selections using NMA, and this strategy and is expected to make a therapeutic breakthrough over traditional chemotherapies [29,30]. In the scope of these eleven interventions researched, some were indicative of significant efficacies when compared with the conventional salvage regimen.…”
Section: Discussionmentioning
confidence: 99%